Efektivitas Pelatihan Pertolongan Pertama Henti Jantung Dengan Model Selamat Terhadap Self Efikasi Masyarakat Kota Pontianak - Nurpratiwi; Hidayat, Uti Rusdian; Hatmalyakin, Debby; Alfikrie, Fauzan; Akbar, Ali; Amaludin, Mimi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2022)
Out-Of-Hospital Cardiac Arrest (OHCA) Is A Condition That Often Threatens A Person's Life. Of The Many Events Of Cardiac Arrest, Only A Few Victims Can Survive. This Condition Is Related To The Low Rate Of First Aid For Cardiac Arrest In The Community And The Speed Of Health Workers Can Reach The Scene. This Condition Arises Because First Responders Lack Confidence In Performing First Aid In Cardiac Arrest. This Study Aims To Analytic The Effectiveness Of Cardiac Arrest First Aid Training With The SELAMAT Model For Self-Efficacy The People Of Pontianak City. This Study Used A Quasi-Experimental Research With A Pretest-Posttest Approach With A Control Group. The Intervention And Control Groups Each Consisted Of 30 People. The Instruments Used Are Questionnaires And Statistical Tests Using Marginal Homogeneity. The Results Showed That Cardiac Arrest First Aid Training With The SELAMAT Model Was Effective In Increasing The Self-Efficacy Of The People In Pontianak City With P Value 0.000. The "SELAMAT" Model Training Is One Of The Training Models That Can Increase The Community's Self-Efficacy In Providing First Aid For Cardiac Arrest.